‘Con nuestro propio esfuerzo’: Understanding the Relationships between International Migration and the Environment in Guatemala - Aguilar-Støen, Mariel (European Review of Latin American and Caribbean Studies, 2012)
Abstract:International migration from rural areas affects the environment in numerous and complex ways. The inflow of economic and social remittances changes production and consumption patterns, social relations, and social and economic institutions in the places of origin of migrants. In this case study, I discuss how migration is pushing a local process of land redistribution in Guatemala. Such a process is also changing patterns of land use and land cover. The process is influenced by the emergence of local cooperatives, which in turn are stimulated by organizations and networks in wider temporal and spatial contexts. Land acquisition by migrant families has also improved their position vis-àvis traditional landowners. My study suggests that in contexts where local organization is successful and linked to actors and networks at wider scales, transnational households are in a good position to negotiate the outcomes of the use of remittances. These families are improving their living standards without degrading the environment irreversibly.Resumen: ('Con nuestro propio esfuerzo': Comprendiendo la relación entre la migración internacional y el medio ambiente en GuatemalaLa migración internacional de las zonas rurales afecta el medio ambiente de maneras significantes y complejas. El ingreso de las remesas económicas y sociales cambian los patrones de producción y consumo; las relaciones sociales y las instituciones sociales y económicas en los lugares de origen de los migrantes. En este estudio de caso, se analiza cómo la migración está impulsando un proceso local de redistribución de la tierra en Guatemala. Este proceso también está afectando los patrones de uso del suelo. Asimismo, este proceso está influenciado por el surgimiento de cooperativas locales, que a la vez son estimuladas por organizaciones y redes en amplios contextos temporales y espaciales. Adquisiciones de tierras por familias de inmigrantes también ha mejorado su posición con respecto a los terratenientes tradicionales. Este estudio sugiere que en contextos donde la organización local tiene éxito y vinculado a actores y redes a escalas más amplias; las familias transnacionales están en una buena posición para negociar resultados de la utilización de las remesas. Estas familias están mejorando su nivel de vida sin degradar el medio ambiente irreversiblemente.